1994
DOI: 10.1116/1.587547
|View full text |Cite
|
Sign up to set email alerts
|

Long-term reliability of Pt and Mo diffusion barriers in Ti–Pt–Au and Ti–Mo–Au metallization systems for GaAs digital integrated circuits

Abstract: Reliability of Ti–Pt–Au and Ti–Mo–Au systems has been investigated for GaAs integrated circuit first-level metallizations on semi-insulating GaAs substrates and second-level metallizations on interlayer SiO2 films using Auger depth profile analysis, residual resistance examination and temperature storage step-stress testing. Auger analysis and residual resistance examination showed significant reaction between first-level Ti–Pt–Au and GaAs substrates during metallization processes, while Ti–Mo–Au system with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…3). Meanwhile, as reported by several authors [6,7], Pt acts as a barrier to the diffusion of Au into the Ti as confirmed by the analysis (Fig. 5(b)).…”
Section: Chemical Propertiessupporting
confidence: 86%
“…3). Meanwhile, as reported by several authors [6,7], Pt acts as a barrier to the diffusion of Au into the Ti as confirmed by the analysis (Fig. 5(b)).…”
Section: Chemical Propertiessupporting
confidence: 86%
“…Each TLP stack contains material diffusion barrier layers to contain the gold and indium materials through processing and over its lifetime. Each of the Au-In TLP bonds are sandwiched within a stack of barrier layers of tungsten for adhesion, titanium as the primary diffusion barrier, and platinum to prevent undesirable Au-Ti intermetallics [8], [9]. These barrier layers also ensure the ratio of indium to gold remains constant.…”
Section: B Experimentsmentioning
confidence: 99%
“…These particular metals were chosen, since they are commonly used for ohmic contacts in III-V materials. [2][3][4][5][6] Pt and Ti tend to have a fairly smooth diffusion profile when annealed at our maximum processing temperature of 300°C. [2][3][4] Although Pd and Au have rougher diffusion profiles, some work has indicated that if they are thin enough, they may also be used.…”
Section: Introductionmentioning
confidence: 95%
“…[2][3][4][5][6] Pt and Ti tend to have a fairly smooth diffusion profile when annealed at our maximum processing temperature of 300°C. [2][3][4] Although Pd and Au have rougher diffusion profiles, some work has indicated that if they are thin enough, they may also be used. 5 Furthermore, Pt is an excellent diffusion barrier to Au at our processing temperature of 300°C, provided it is thick enough to avoid pinholes or other defects, so Au can be used as the top metal for all of the subsequent interconnects.…”
Section: Introductionmentioning
confidence: 95%